Understanding the interplay between teacher self-efficacy, teacher–student interactions, and students’ self-regulated learning skills at different levels of classroom ecology - de Ruig, Niels J.; Zee, Marjolein; de Jong, Peter F. (Frontiers in Education, 2024)
Studies pinpoint the importance of exploring factors in the classroom environment that might foster students' SRL-skills in various domains. This study explored specific teacher and classroom factors, including self-efficacy for SRL-skills (TSE) and teacher-student interactions in relation to students' self-regulated learning skills in various domains (metacognitive, motivational, and behavioral). Additionally, the moderating role of teacherstudent interactions in the relationship between TSE and SRL-skills was examined. Third-to sixth grade students (N = 1278, 46.9% boys) from 63 classrooms of Dutch elementary schools completed reports about their metacognitive, motivational, and behavioral SRL-skills.Teachers reported on their TSE for eight randomly selected students from their classes. In addition, the Classroom Assessment Scoring System was used to observe the quality of teacher-student interactions. Multilevel analyses generally revealed that individual students reported better metacognitive, motivational, and behavioral SRL-skills when their teachers felt efficacious in teaching SRL-skills. However, none of the associations at the class level were significant. Moreover, when high-quality teacher-student interactions were observed, students reported lower levels of metacognitive, motivational, and behavioral SRL-skills. No moderating effect of teacher-student interactions on the relation between TSE and SRL-skills was found. These findings show that specific measures of TSE at the appropriate level of analysis may help to better explain variation in TSE and students' SRL-skills.